(untitled) (Quinto Sol, 2024)
This dossier is made of original articles that delve into the history of youth (understood as a sociocultural category based upon age) and of young women and men (understood as cultural and political actors). Besides collaborating with the expansion of the history of youth, the articles amplify our understanding of the recent past, chiefly spanning from the 1960s to the 1980s. The articles likewise focus on different geographical scales (local, national, transnational) to account for the complexity of the sociocultural history of youth.